Efficient production of fatty acids and lycopene from Gac aril by flash extraction - LI, Yuan; LIU, Zeyuan; XU, Tao; LIU, Chunqiao (Food Science and Technology, 2023)
The aim of the study was to develop an efficient and cost-effective method for fatty acids and lycopene separation from Gac aril by using flash extraction. The extraction efficiency (EE) of fatty acids and lycopene was investigated. When 22 mL of anhydrous ethanol per gram of solid was agitated at 3,000 rpm (revolutions per minute) for 100 s, the highest EE of fatty acids reached 88.48%, and then 98.27% was achieved after saponification refining. After fatty acid extraction, lycopene was extracted from the residues of the Gac arils, and the maximum EE of lycopene was 94.86% by using 24 mL of petroleum ether per gram of solid with agitation rate at 4,000 rpm for 40 s. 97.20% was achieved after crystallization purification. In conclusion, flash extraction is a promising approach that will enhance the utilization of Gac fruit from Gac processing for use in the food and pharmaceutical industries.